Characterization of two novel colistin resistance gene mcr-1 variants originated from Moraxella spp. - Che, Yongliang; Wu, Renjie; Li, Hongjie; Wang, Longbai; Wu, Xuemin; Chen, Qiuyong; Chen, Rujing; Zhou, Lunjiang (Frontiers in Microbiology, 2023)
The aim of this study was to characterize two novel mcr-1 variants, mcr-1.35 and mcr-1.36, which originated from Moraxella sp. that were isolated from diseased pigs in China. The Moraxella sp. carrying novel mcr-1 variants were subjected to whole-genome sequencing (WGS) and phylogenetic analysis based on the 16S rRNA gene. The mcr-1 variants mcr-1.35 and mcr-1.36 were characterized by phylogenetic analysis, a comparison of genetic environment and protein structure prediction. WGS suggested that two novel mcr-1 variants were located in the chromosome of three Moraxella sp. with a genetic environment of mcr-1-pap2. In addition to the novel colistin resistance genes mcr-1.35 and mcr-1.36, the three Moraxella sp. contained other antimicrobial resistance genes including aac(3)-IId, tet(O), sul2, floR, blaROB-3, etc. A functional cloning assay indicated that either the mcr-1.35 or mcr-1.36 gene could confer resistance to colistin in Escherichia coli DH5α and JM109. The nucleotide sequences of mcr-1.35 and mcr-1.36 presented 95.33% and 95.33% identities, respectively, to mcr-1.1. The phylogenetic analysis showed that mcr-1.35 and mcr-1.36 originated from Moraxella sp. belonging to subclades distinct from those of mcr-1 variants (mcr-1.1 to mcr-1.34 except mcr-1.10) originating from Enterobacteriaceae. The deduced amino acid sequences of MCR-1.35 (MCR-1.36) showed 96.67% (96.49%), 82.59% (82.04%), 84.07% (83.52%), 55.52% (55.17%), 59.75% (59.57%) and 61.88% (61.69%) identity to MCR-1.10, MCR-2.2, MCR-6.1, MCR-LIN, MCR-OSL and MCR-POR, respectively, that originated from Moraxella sp.. Notably, protein structure alignment showed only a few changes in amino acid residues between MCR-1.1 and MCR-1.35 as well as MCR-1.1 and MCR-1.36. In conclusion, this study identified Moraxella sp. carrying two novel mcr-1 variants, mcr-1.35 and mcr-1.36, conferring resistance to colistin, which were isolated from pig farms in China. Meanwhile, mcr-like variants were identified to reserve in chromosome of some species of Moraxella isolated from pig samples.